2021
DOI: 10.1371/journal.pmed.1003731
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal hormone therapy and women’s health: An umbrella review

Abstract: Background There remains uncertainty about the impact of menopausal hormone therapy (MHT) on women’s health. A systematic, comprehensive assessment of the effects on multiple outcomes is lacking. We conducted an umbrella review to comprehensively summarize evidence on the benefits and harms of MHT across diverse health outcomes. Methods and findings We searched MEDLINE, EMBASE, and 10 other databases from inception to November 26, 2017, updated on December 17, 2020, to identify systematic reviews or meta-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 129 publications
(160 reference statements)
1
88
0
8
Order By: Relevance
“…One likely reason for this is that male patients tend to have more tobacco and alcohol consumption than female patients, both of which are clear risk factors of ESCC and EAC. Moreover, female hormones are reported to be preventive for ESCC and EAC in several previous studies [11][12][13]. Indeed, subgroup analysis according to age classes showed that the OR of male compared to female for EAC steadily decreased with ageing, while that for ESCC continuously increased (online suppl.…”
Section: Discussionmentioning
confidence: 86%
“…One likely reason for this is that male patients tend to have more tobacco and alcohol consumption than female patients, both of which are clear risk factors of ESCC and EAC. Moreover, female hormones are reported to be preventive for ESCC and EAC in several previous studies [11][12][13]. Indeed, subgroup analysis according to age classes showed that the OR of male compared to female for EAC steadily decreased with ageing, while that for ESCC continuously increased (online suppl.…”
Section: Discussionmentioning
confidence: 86%
“…Participants were excluded if they were treated with didanosine, an NRTI associated with increased risk of cardiovascular events [ 28 ]. In addition, women were excluded if pregnant, breast feeding, or postmenopausal, to minimize variability of endogenous sex hormones among participants and potential influence on cardiovascular function [ 29 ]. Similarly, persons on gender reaffirming hormone therapy in the previous year were also excluded.…”
Section: Methodsmentioning
confidence: 99%
“…An umbrella review including five prospective cohort studies with 163,161 women reported that MHT use was associated on average with a 1.41-fold (95% CI 1.09–1.81) increased risk of new-onset asthma compared to non-use. 65 Similarly, in a recent nested case-control study based on the Danish registers, 66 which included 34,533 women with asthma and 345,116 without asthma aged 40–65 years, use of MHT and its subtypes (estrogen-alone therapy and estrogen plus progestin therapy) was associated with an increased risk of developing asthma, with HRs ranging from 1.18 to 1.63. However, these results were contrasted by a UK national retrospective cohort study, 62 the largest longitudinal study on the topic to date, which included 353,173 women aged 46–70 years with 1,340,423 person-years of follow-up, and found that use of MHT and its subtypes was associated with a decreased risk of asthma, with HRs ranging from 0.78 to 0.89, and that longer duration of use was associated with a decreased asthma risk in a dose-response manner.…”
Section: Epidemiological Evidence On Sex Hormones and Asthma Onsetmentioning
confidence: 99%
“… Hormonal contraceptives The evidence on hormonal contraceptives and asthma is mixed: the UK national cohort study 64 of 564,896 women and a German community-based cohort study 63 of 1191 women reported that use of hormonal contraceptives was associated with a decreased risk of new-onset asthma compared to non-use, and that longer duration of use was associated with a lower asthma risk than shorter duration 64 ; however, the Nurses’ Health Study 59 of 36,094 women found that use of hormonal contraceptives was associated with an increased asthma risk. Menopausal hormone therapy (MHT) The evidence on MHT and asthma is mixed: an umbrella review 65 including five cohort studies with 163,161 women and a Danish register-based nested case-control study 66 of 379,649 women reported that use of MHT was associated with an increased risk of new-onset asthma compared to non-use; however, the UK national cohort study 62 of 353,173 women found that use of MHT was associated with a decreased asthma risk, and that longer duration of use was associated with a lower asthma risk than shorter duration. Serum levels of sex hormones A cross-sectional study 67 reported that an elevated serum level of estradiol was associated with decreased odds of current asthma in both women and men.…”
Section: Age- and Gender-related Disparities In Asthmamentioning
confidence: 99%